Changes in Hippocampal Volume are Correlated with Cell Loss but Not with Seizure Frequency in Two Chronic Models of Temporal Lobe Epilepsy - Polli, Roberson S.; Malheiros, Jackeline M.; dos Santos, Renan; Hamani, Clement; Longo, Beatriz M.; Tannús, Alberto; Mello, Luiz E.; Covolan, Luciene (Frontiers in Neurology, 2014)
Kainic acid (KA) or pilocarpine (PILO) have been used in rats to model human temporal lobe epilepsy but the distribution and severity of structural lesions between these two models may differ. Magnetic resonance imaging (MRI) studies have used quantitative measurements of hippocampal T2 (T2HP) relaxation time and volume, but simultaneous comparative results have not been reported yet. The aim of this study was to compare the MRI T2HP and volume with histological data and frequency of seizures in both models. KA- and PILO-treated rats were imaged with a 2T MRI scanner. T2HP and volume values were correlated with the number of cells, mossy fiber sprouting and SRS frequency over the 9 months following SE. Compared to controls, KA-treated rats had unaltered T2HP, pronounced reduction in hippocampal volume and concomitant cell reduction in granule cell layer, CA1 and CA3 at 3 months post SE. In contrast, hippocampal volume was unchanged in PILO-treated animals despite detectable increased T2HP and cell loss in granule cell layer, CA1 and CA3. In the following 6 months, MRI hippocampal volume remained stable with increase of T2HP signal in the KA-treated group. The number of CA1 and CA3 cells was smaller than age-matched CTL group. In contrast, PILO group had MRI volumetric reduction accompanied by reduction in the number of CA1 and CA3 cells. In this group, T2HP signal was unaltered at 6 or 9 months after status. Reductions in the number of cells were not progressive in both models. Notably, the SRS frequency was higher in PILO than in the KA model. The volumetry data correlated well with tissue damage in the epileptic brain, suggesting that MRI may be useful for tracking longitudinal hippocampal changes, allowing the assessment of individual variability and disease progression. Our results indicate that the temporal changes in hippocampal morphology are distinct for both models of TLE and that these are not significantly correlated to the frequency of SRS.